As atividades como disparadoras da análise do processo de trabalho de terapeutas ocupacionais na Atenção Básica em Saúde - Pugliero, Beatriz (Universidade Federal de São Carlos, 2023)
Introduction: The literature points to a diversity of possibilities of action for Occupational Therapy in the context of Primary Health Care. The occupational therapist is responsible for detecting individual and group needs and difficulties and proportions of actions, through general activities. An approach on the use of different forms of activities is described by several authors. Thus, in the scope of understanding the use of activities by the occupational therapist inserted in Primary Health Care, we seek to analyze different actions aimed at carrying out and developing the use of activities in professional practice. Objective: To understand the use of activities by the occupational therapist inserted in Primary Health Care. Methodology: Study with an exploratory methodology with a qualitative approach. Study participants were Occupational Therapists working in Primary Health Care in a medium-sized city in the interior of São Paulo. For the development of the research, the Photovoice method was used. The visual material, the individual interviews and the narratives that accompanied them were the main focus of analysis and study in this research. Results: The study showed a diversity of possibilities for acting and producing activities for Occupational Therapy in the context of Primary Health Care, the work performed includes individual and group care, matrix support and permanent education. While the use of activities takes place as a diagnosis, linking, as a possibility of transformation, stimulation of cognitive/motor/communication skills, for reception, individual and group intervention, as well as an extension of the subject's daily life beyond the service.
Activities as process analysis triggers of work of occupational therapists in Primary Health Care
Keywords: Atividades; Atenção Básica em Saúde; Terapia Ocupacional; Photovoice; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL